Description Of Self-Efficacy In Diabetes Millitus Patients At Bagor Health Center - Sony Wahyu Tri Cahyono (Journal for Research in Public Health, 2024)
In theory, self-efficacy provides scientific reasons as a strategy that has the potential to increase an individual's self-confidence in their ability to make behavior changes. Self-efficacy in individuals with diabetes mellitus is related to certain situations, circumstances, environments and tasks. The aim of this study was to determine the description of self-efficacy in diabetes mellitus patients at PUSKESMAS Bagor. The research design used in this research is descriptive, namely research that aims to describe or explain important events that occur today. The research was conducted on January 24 2024 on diabetes mellitus patients. The population of diabetes mellitus patients was 110 patients who took part in the prolanis program at PUSKESMAS Bagor. Using an incidental sampling technique, the sample size was 97 respondents. Self-efficacy variables. data collection using a questionnaire. The research results showed that of the 97 respondents, 58 respondents (60%) had good criteria, 32 respondents (33%) had sufficient criteria and 7 respondents (7%) had poor criteria. Self-efficacy is important for diabetes mellitus sufferers to always maintain health, especially in controlling blood sugar levels within normal limits.